Evolution of the research on Paleontology of marine invertebrates in the Central American Journal of Geology - Aguilar, Teresita (2014)
: Fossil marine invertebrates are a very important group in Costa Rica and sourthen Central América, due to their abundance and high diversity and a strong relationship with geological processes, depositional environments and sometimes their restriction to short periods of time. Among the invertebrates Mollusks are dominant, followed by Arthropods, Echinodermata, Coelenterata, Porifera, Brachiopoda, Bryozoa and Annelida. These are showed in the scarcity of articles concerning to fossil invertebrates in the RGAC (13 in total), mainly about Mollusks (44 %), primarily from Neogene (62%) and mostly found in Costa Rica (85%)